2015
DOI: 10.3892/mmr.2015.3540
|View full text |Cite
|
Sign up to set email alerts
|

Agmatine protects Müller cells from high-concentration glucose-induced cell damage via N-methyl-D-aspartic acid receptor inhibition

Abstract: Neural injury is associated with the development of diabetic retinopathy. Müller cells provide structural and metabolic support for retinal neurons. High glucose concentrations are known to induce Müller cell activity. Agmatine is an endogenous polyamine, which is enzymatically formed in the mammalian brain and has exhibited neuroprotective effects in a number of experimental models. The aims of the present study were to investigate whether agmatine protects Müller cells from glucose-induced damage and to expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 42 publications
1
5
0
Order By: Relevance
“…31) Lee et al found that HG could inhibit mTORC1 activity. 33) Our results verified this report by revealing that mTOR signaling pathway may be associated with HGinduced apoptosis in HK-2 cells. However, these effects were alleviated in the presence of miR-15b-5p mimics, demonstrating that miR-15b-5p mimics activated mTOR signaling pathway via increasing the level of p-Akt, p-mTOR and p-p70S6K.…”
Section: Discussionsupporting
confidence: 89%
“…31) Lee et al found that HG could inhibit mTORC1 activity. 33) Our results verified this report by revealing that mTOR signaling pathway may be associated with HGinduced apoptosis in HK-2 cells. However, these effects were alleviated in the presence of miR-15b-5p mimics, demonstrating that miR-15b-5p mimics activated mTOR signaling pathway via increasing the level of p-Akt, p-mTOR and p-p70S6K.…”
Section: Discussionsupporting
confidence: 89%
“…Agmatine (decarboxylated arginine) is an endogenous polyamine synthesized via decarboxylation of l -arginine by arginine decarboxylase. 10 , 11 As shown in a previous study, agmatine has oxygen radical-scavenging effects (antioxidant activity), protects mitochondrial function, and confers resistance to cellular apoptosis. 12 The agmatine-induced protection of mitochondria is presumed to be a key mechanism of action, and agmatine effectively inhibits ROS-induced activation of BAX.…”
Section: Introductionmentioning
confidence: 82%
“…These alterations lead to the activation of cell death pathways. Apoptosis is described due to a decrease in Bcl-2 and an increase in Bax (bcl2 associated X) and caspase-3 levels [173][174][175]. Recently, several studies have shown the activation of pyroptosis and mitophagy/autophagy pathways [169,[176][177][178][179][180].…”
Section: Müller Cells In Drmentioning
confidence: 99%